SIKAP ANAK DENGAN GANGGUAN EMOSI DAN TINGKAH LAKU TERHADAP PERILAKU ASERTIF DI SEKOLAH LUAR BIASA - Shintesa Mayu Fitriya; Hartini Nara (Perspektif Ilmu Pendidikan, 2010)
This research aims to improve speaking skills through watching videos kids children stories of children aged 5-6 years in kindergarten Islam Al-Fattah, Wanasari Village, Bekasi regency.The methodology uses a classroom action research which conduct through two cycle consists of planning, action, observation, and reflection. Subjects are 10 children in group B who have problems with aspects of speech. Data collection techniques use non-test consists of observation, interview, and documentation. The analysis techniques use two paradigms that is mean, medium, modus, proportion study with a minimum percentage increase to 71% for quantitative paradigm, and data reduction, data display, conclusion/verification for qualitative paradigm.